Comparison of Hemodynamic Stability and Pain Control in Lateral and Prone Positions in Patients Undergoing Percutaneous Nephrolithotomy: A Randomized Controlled Trial - Roodneshin, Fatemeh; Poor Zamany Nejat Kermany, Mahtab; Rostami, Pooya; Ahmadzadeh, Narges; Gharaei, Babak; Kamranmanesh, Mohammad Reza (Urology Journal, 2020)
Purpose: Percutaneous nephrolithotomy (PCNL) is the preferred surgical treatment in many cases of kidney stones which is performed in different positions such as prone, lateral, and supine. This study was designed to evaluate whether patient position (lateral versus . prone) has an effect on the need for analgesia and onset of pain after surgery. Materials and Methods: Patient with confirmed kidney stones (size ? 2 cm) who were candidates for PCNL were enrolled in this study. The required biochemical analyses were performed preoperatively. All patients underwent spinal anesthesia by the same anesthesiologists and then were randomly divided into two separate groups as lateral (L) and prone (P) positions. The operations’ start and end time, required time for proper access into target calyces, additional need for analgesic or cardiac drugs, duration of analgesia, and onset of pain after PCNL were carefully recorded and then compared between the two groups. Results: In total, 51 patients were evaluated of whom 39 were men and 12 were women. Mean duration of analgesia after PCNL surgery in P group (173 ± 8 min) was significantly longer than in L group (147±12 min) (P = .001). Furthermore, the amount of ephedrine usage in L group (3.6 ± 1.5mg) was significantly lower than in the P group (16.4 ± 12mg), suggesting more hemodynamic variations in the P group during the operation. Conclusion: Our randomized control trial study shows that choosing the optimal position in the PCNL technique depends on patient’s condition. If hemodynamic control is of matter to the anesthesiologist, then lateral position is more appropriate. However, if control of pain and longer time of analgesia are important, prone position may be preferred.